English language in the scope of multiliteracies of military higher education - Barros Junior, Arlindo José de; Freire Junior, João; Bussolotti, Juliana Marcondes (Debates em Educação, 2021)
The article aims to analyze the perception of students from a Military Higher Education Institution regarding the applicability of the English language in their future career as Brazilian Army (EB) combatant officers. It is a survey that focuses on the analysis of local phenomena. To this end, applied research of descriptive character with a quantitative and qualitative approach was carried out. The results obtained were achieved inductively and identified that (a) the English Language contributes to the student’s individual process of attributing meaning to the multiple literacies inherent in the military career and; (b) the student's ideas regarding the use of the English language in his future career is not limited to communication with foreign agents, but also encompasses daily military activities and.